Sensitivity analysis in linear bilevel programs - Izadi Boroumand, S.; Zohrehbandian, Majid (Journal of Informatics and Mathematical Sciences, 2017)
Sensitivity analysis is the study of changing in the input parameters of the original problem and description of their impacts on the optimal solution. Sensitivity analysis is important in practice, where parameter values of the practical problems may be estimates. This paper studies the link between sensitivity analysis of linear programming problem where there are extensive literature on it, and the sensitivity analysis of the linear bilevel programming problem. Numerical examples are provided to illustrate the approach.